Effect of organic manures and inorganic fertilizers on dry matter yield, soil and plant nutrient content in onion (Allium cepa) - NEGI, MANISHA; SHARMA, JAGJEET CHAND; SHUKLA, YOG RAJ (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted to study the effect of different sources of organic manures [Farmyard manure (FYM),Vermicompost (VC) and Jeevamrut] and inorganic fertilizers (Urea, SSP and MOP) on soil and plant nutrient content in onion (Allium cepa L.) during 2017–18 and 2018–19 at Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh. The experiment was laid out in randomized block design with nine treatments replicated thrice. Soil samples from all the treatments during both the years were collected from 0–15 cm depth. At the end of the experiment, significantly high post-harvest fertility status of macronutrients (NPK), viz. 386, 1566 and 384.1 kg/ha, respectively, were recorded under recommended nutrient management practice (RDF) i.e. 125 N: 75 P: 60 K kg/ha + FYM @250 q/ha. Similarly, significantly highest concentration of bulb and leaf macronutrients and biomass yield of bulbs and leaves were recorded under RDF. The purely organic module besides excelling at par with RDF in build-up of macronutrients in soil also registered maximum organic carbon content in soil. From the study, it can be inferred that RDF + FYM @250 q/ha can be used for maintaining the soil fertility.